Health Complaints and Health Insurance Ownership as Determinants of Health Service Utilization among Women of Childbearing Age in Indonesia: Aggregate Data Analysis of the 2025 Health Statistics Profile - Reny Mareta Sari; Niken Agus Tianingrum (Open Access Health Scientific Journal, 2026)
Background: Women of childbearing age have greater healthcare needs because they require both general and reproductive health services. Nevertheless, healthcare utilization remains suboptimal and may be influenced by health complaints and health insurance ownership. This study aimed to analyze the influence of health complaints and health insurance ownership on healthcare utilization among women of reproductive age in Indonesia.Methods: This quantitative analytical study employed an ecological (aggregate) design using secondary data from the Indonesia Health Statistics Profile 2025 published by Statistics Indonesia (BPS). The unit of analysis encompasses 38 provinces in Indonesia. The dependent variable was the proportion of women of reproductive age with health complaints who utilized outpatient healthcare services. Independent variables included the proportion of women experiencing health complaints that interfered with daily activities and the proportion of women owning health insurance. The data were analyzed descriptively, followed by scatter plot visualization and multiple linear regression analysis.Results: The results showed health complaints demonstrated a positive trend with healthcare utilization but were not statistically significant (p = 0.305). In contrast, health insurance ownership was significantly associated with healthcare utilization (p = 0.013). Provinces with higher health insurance coverage tend to have higher healthcare utilization among women of reproductive age. Health insurance ownership is a significant determinant of healthcare utilization among women of reproductive age in Indonesia, whereas health complaints alone do not significantly influence healthcare utilization.Conclusion: Expanding health insurance coverage may reduce financial barriers and improve equitable access to healthcare services, particularly for women of reproductive age.